Influence of overweight and childhood obesity on physical fitness according to socioeconomic level - Myriam Guerra-Balic; Josep Cabedo Sanroma; Francesca Sánchez-Martínez; Gemma Serral-Cano; Josep Sánchez-Malagón; Carles Ariza-Cardenal (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Overweight and childhood obesity has increased its prevalence.